Effect of sintering parameters on the density, microstructure and mechanical properties of the niobium-modified heat-resistant stainless steel GX40CrNiSi25-20 produced by MIM technology - Butković, Samir (Materiali in tehnologije, 2012)
Properties of heat-resistant, stainless-steel parts produced by the metal-injection-molding (MIM) process depend mostly on the sintering parameters. The effect of these sintering parameters on the densification, microstructure, hardness and tensile properties of the niobium-modified, heat-resistant stainless steel GX40CrNiSi25-20 were investigated. The prepared feedstock was injection molded to obtain tensile test specimens (ISO 2740). The debinding of the molded parts was performed using the catalytic debinding method, while the residual binder was removed by thermal debinding. The sintering was performed at 1200 °C and 1310 °C, in argon (Ar), hydrogen (H2) and nitrogen (N2) atmospheres, with the sintering times between 3 h and 6h. It was found that sintering in a nitrogen atmosphere increased the strength and reduced the ductility. The mechanical properties were also enhanced by a higher sintering temperature (1310 °C), due to the positive effects of the pore rounding and increased density. The prolonged sintering time caused changes in the grain size, but had little effect on the density. Faster sintering and improved ductility was observed for the samples sintered in hydrogen and argon atmospheres.
Keywords: metal injection molding; praškasti materiali; ognjevzdržno nerjavno jeklo; heat-resistant stainless steel; sintering parameters; sintranje; density; gostota; microstructure; mikrostruktura; mechanical properties; mehanske lastnosti; metal powder